PENGARUH SALES PROMOTION DAN STORE ATMOSPHERE TERHADAP POSITIVE EMOTION DAN PERILAKU IMPULSE BUYING DI DEPARTEMENT STORE MATAHARI DUTA MALL, BANJARMASIN - Adista Anjar Diany; Marijati Sangen; Faisal (JWM (JURNAL WAWASAN MANAJEMEN), 2019)
The purpose of this study was to analyze and find out the effects of sales promotion and store atmosphere on positive emotion and impulse buying at Matahari Departement Store, Duta Mall, Banjarmasin. This research used Non Probability Sampling and Purposive Sampling Technique, with the sample of 148 respondents who were the customers of Matahari Departement Store, Duta Mall, Banjarmasin. The instrument of this research was questionnaires and data were analyzed with Structural Equation Modeling (SEM). The results of the analysis proved that the sales promotion did not have significant effects on positive emotion and impulse buying but store atmosphere had significant effects on positive emotion and impulse buying. Also, positive emotion had significant to the impulse buying of the consumers. Store atmosphere was created by Matahari Departement Store, Duta Mall, Banjarmasin to increase the feelings of satisfaction, comforts and enjoyment when shopping. The highest CR value was positive emotion which had significant effects on impulse buying. It is suggested that Matahari Departement Store, Duta Mall, Banjarmasin should prioritize in increase impulse buying to create positive emotion first. Positive emotion can be established by observing the atmosphere inside and outside outlets such as: music, store design and lighting. Matahari Departement Store, Duta Mall, Banjarmasin also has to make more variations of sales promotions to attract customers to continue shopping. Matahari Departement Store also has to make more variations of sales promotion to attract customers to continue to be in the store. Matahari Department Store should reduce the existing requirements to use given promotions and has regular promotions but not too routine. This allows the consumers to feel getting benefits in a number of existing promotions.